0383 Outdoor Artificial Light at Night, Sleep Duration, and Sleep Quality in the California Teachers Study Cohort. (27th May 2020) - Zhong, C; Franklin, M; Wiemels, J; Chung, N; Benbow, J; Wang, S S; Lacey, J V; Longcore, T
Abstract: Introduction: Artificial light at night (ALAN) is believed to disrupt sleep by suppressing melatonin and altering normal circadian patterns. We assessed the association between self-reported sleep measures and outdoor ALAN in a large cohort of women. Methods: The California Teachers Study (CTS) is a prospective cohort of 133, 479 current and former Californian female public school professionals recruited and given a baseline questionnaire in 1995-1996. A follow-up questionnaire in 2012-2014 assessed self-reported measures of sleep habits, quality, and chronotype. Using geocoded residential addresses, participants were assigned exposures to outdoor ALAN based on the New World Atlas of Artificial Night Sky Brightness to assess the association between ALAN and self-reported sleep initiation, duration, and quality. Results: Of the 42, 706 women who completed the follow-up questionnaire and reported the same sleep patterns over the previous year, 5, 968 reported poor sleep quality. The median outdoor ALAN was 2.16 (IQR: 1.04-3.61) millicandela per meter squared (mcd/m 2 ). After adjusting for self-reported chronotype, use of sleep medication, age, race, and socioeconomic status, residing in the highest ALAN quintile was associated with poor sleep (OR 1.16, 95% CI 1.07-1.26). There did not appear to be an association between outdoor ALAN and time taken to fall asleep (OR 1.02, 95% CI 0.96-1.08), but it was associated with sleeping less than 8 hours (OR 1.41, 95% CI 1.33-1.50). Conclusion: CTS participants who self-reported shorter sleep and poorer sleep quality were more likely to reside in areas with greater levels of outdoor ALAN. We did not see an association with ALAN and time to fall asleep, suggesting ALAN may be contributing to later sleep time or earlier waking. As we continue to follow this cohort, the data collected over the past 20 years provide a rich resource for studying both factors related to sleep and its effect on health. Support: The California Teachers Study and the research reported in this publication were supported by the National Cancer Institute of the National Institutes of Health under award number U01-CA199277; P30-CA033572; P30-CA023100; UM1-CA164917; R01-CA077398; and R01-CA207020.